Development of a Critical Nitrogen Dilution Curve Based on Leaf Area Duration in Wheat - Wang, Xiaolong; Ye, Tianyang; Ata-Ul-Karim, Syed Tahir; Zhu, Yan; Liu, Leilei; Cao, Weixing; Tang, Liang (Frontiers in Plant Science, 2017)
Precise quantification of plant nitrogen (N) nutrition status is essential for crop N management. The concept of critical N concentration (Nc) has been widely used for assessment of plant N status. This study aimed to develop a new winter wheat Nc dilution curve based on leaf area duration (LAD). Four field experiments were performed on different cultivars with different N fertilization modes in the Yangtze River basin and Yellow River basin in China. Results showed that the increase in LAD with increasing cumulative thermal time took the shape of an ‘S’ type curve; whereas shoot N concentration decreased with increasing LAD, according to a power function. Both LAD and shoot N concentration increased with increasing N application. The new LAD based Nc dilution curve was determined and described as Nc=1.6774LAD-0.37 when LAD＞0.13. However, when LAD ≤ 0.13, Nc was constant and can be calculated by the equation when LAD=0.13. The validation of Nc dilution curve with dataset acquired from independent experiments confirmed that N nutrition index (NNI) predictions based on the newly established Nc dilution curve could precisely diagnose N deficiency at different plant growth stages. The integrated N nutrition index (NNIinte), which was obtained by the weighted mean of NNI, was used to estimate shoot N concentration, shoot dry matter, LAD, and yield using regression functions. The linear relationships between NNIinte and these growth variables were well correlated. These results provided enough evidence that the new LAD–based Nc dilution curve could effectively and precisely diagnoses N deficiency in winter wheat crops.